A force for change : how leadership differs from management - Kotter, John P. (New York : The Free Press, 1990)
Introduction. -- Management and leadership, 3. -- Leadership in action, 19. -- The process of Leadership. -- Establishing direction, 35. -- Aligning people, 49. -- Motivating and inspiring, 61. -- The structure of leadership. -- Multiple roles, 77. -- Thick informal networks, 89. -- The origins of leadership. -- Heredity and childhood, 103. -- Career experiences, 113. -- Corporate culture, 127.